SIMULATION AND EXPERIMENTAL STUDY ON THE TURNING MOTION SNAKING CONVEYOR BASED ON MATLAB - ZHANG DongSheng; LI Yan; WANG JinCheng; YU HaiYang; ZHAO XiBei (Jixie qiangdu)
The hunting conveyor as research object, the hunting conveyor motion based on Serpenoid curve shape description, and carries on the discrete design and time domain expansion, using MATLAB software to find the optimal parameters of interval turning movement of the conveyor system. The simulation analysis is carried out on three kinds of working conditions, such as serpentine motion, left turn and right turn, and the variation of the steering angle is obtained under different working conditions. Finally, according to the frame turning experiment of vehicle hunting conveyor angle, verify the validity and rationality of the turning motion control parameters.